Avian Embryonic Culture: A Perspective of In Ovo to Ex Ovo and In Vitro Studies - Sukparangsi, Woranop; Thongphakdee, Ampika; Intarapat, Sittipon (Frontiers in Physiology, 2022)
The avian embryos growing outside the natural eggshell (ex ovo) were observed since the early 19th century, and since then chick embryonic structures have revealed reaching an in-depth view of external and internal anatomy, enabling us to understand conserved vertebrate development. However, the internal environment within an eggshell (in ovo) would still be the ideal place to perform various experiments to understand the nature of avian development and to apply other biotechnology techniques. With the advent of genetic manipulation and cell culture techniques, avian embryonic parts were dissected for explant culture to eventually generate expandable cell lines (in vitro cell culture). The expansion of embryonic cells allowed us to unravel the transcriptional network for understanding pluripotency and differentiation mechanism in the embryos and in combination with stem cell technology facilitated the applications of avian culture to the next levels in transgenesis and wildlife conservation. In this review, we provide a panoramic view of the relationship among different cultivation platforms from in ovo studies to ex ovo as well as in vitro culture of cell lines with recent advances in the stem cell fields.